1993
DOI: 10.21273/hortsci.28.9.891
|View full text |Cite
|
Sign up to set email alerts
|

Yield Components of Day-neutral and Short-day Strawberry Varieties on Raised Beds in British Columbia

Abstract: Eight day-neutral and seven short-day strawberry (Fragaria ×ananassa, Duch.) varieties were evaluated on raised beds during 1990 and 1991 in the Fraser River valley, B.C. Among day-neutral varieties in 1990, total variation in marketable yield originated in fruit count (26%), total yield (18%), average leaf size (22%), and runner count (19%) per plant. In 1991, total variation in marketable yield originated in fruit count (38%), runner count (23%), crown count (13%), and tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…2 comprised nearly 50% of the total biomass values. While these values are within previously reported ranges, others have reported that cultivar, cultural procedures, and year-to-year environmental variation can have significant effects on biomass accumulation and distribution patterns (Baumann et al, 1993;Popenoe and Swartz, 1985).…”
Section: Resultssupporting
confidence: 86%
“…2 comprised nearly 50% of the total biomass values. While these values are within previously reported ranges, others have reported that cultivar, cultural procedures, and year-to-year environmental variation can have significant effects on biomass accumulation and distribution patterns (Baumann et al, 1993;Popenoe and Swartz, 1985).…”
Section: Resultssupporting
confidence: 86%
“…Significance of interaction between C and M is given: ns Not significant, *p < 0.05, **p < 0.01. mass and fruit yield, since day-neutral cultivars can initiate flowers and keep fruiting continuously under mild temperature condition. Strong positive correlation between fruit yield and vegetative growth, such as leaf area and crown number, were observed in DN cultivars (Baumann et al, 1993). Improved production systems that favor vegetative growth may also favor higher yields, as the hydroponic system was more productive than soil beds in the preliminary trial (Ruan et al, 2010).…”
Section: Research Reportmentioning
confidence: 99%
“…Strawberry growers have found high profitability in utilizing the raised bed, or hill plasticulture, system ( , ). This system has advantages of enhanced weed control, advanced harvest, increased yield and fruit size, prevention of bed erosion, and increased fruit cleanliness ( ). There are a wide variety of synthetic mulches that have been used in the raised bed culture system, but black polyethylene mulch has become the standard for the annual production of eastern U.S. strawberries.…”
Section: Introductionmentioning
confidence: 99%